2019
DOI: 10.22454/fammed.2019.641507
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Surrounding a Community-Based Fitness Intervention at an Urban FQHC

Abstract: Background and Objectives: The population surrounding an urban federally qualified health center (FQHC) in Philadelphia has poorer health than Philadelphia overall. Community residents identified aerobics and dance classes as very important services or programs that an FQHC might provide. We sought to measure the impact of participation in a resident physician-led, patient-centered fitness and nutrition class on participants’ attitudes, knowledge, and self-efficacy regarding their health. Methods: An urban lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Health self-efficacy scores of the experimental group significantly increased after the programs, while there were no significant differences in the control group. This is in line with Foster et al [24], who used an eight-week health program targeting community residents and found that health self-efficacy increased after intervention. Health self-efficacy refers to the level of self-confidence perceived as performing general health-promoting behaviors and consists of exercise efficacy, psychological efficacy, nutritional efficacy, and health management efficacy [17].…”
Section: Discussionsupporting
confidence: 90%
“…Health self-efficacy scores of the experimental group significantly increased after the programs, while there were no significant differences in the control group. This is in line with Foster et al [24], who used an eight-week health program targeting community residents and found that health self-efficacy increased after intervention. Health self-efficacy refers to the level of self-confidence perceived as performing general health-promoting behaviors and consists of exercise efficacy, psychological efficacy, nutritional efficacy, and health management efficacy [17].…”
Section: Discussionsupporting
confidence: 90%
“…At present, people are eager to improve their physical quality by participating in physical exercise. Therefore, the social demand for physical fitness is also accumulating [ 1 ]. Moreover, with the development of competitive sports, people began to pay attention to the development of sports and have a certain demand for sports products and venues.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown increased consumption of fruits and vegetables and improved metabolic markers as a result of these programs. 24,25 Although evidence suggests benefits from the WFPB diet, [12][13][14][15][16][17][18][19][20] interventions advocating a transition to this diet are uncommon at FQHCs because of their perceived cost. There may also be a perception that such interventions are irrelevant to FQHC patients.…”
mentioning
confidence: 99%